Effect of propofol combined with remimazolam besylate on blood pressure during general anesthesia induction in patients undergoing gynecological laparoscopic surgery: single-centre randomized controlled trial - Xinmin Zhao; Haigen Xu; Shuping Wang; Yuanyuan Chen; Shuyu Yue (BMC Anesthesiology)
Abstract Background Hypotension often occurs during intraoperative anesthesia induction in gynecological laparoscopic surgery. Remimazolam is reportedly associated with lesser intraoperative hypotension than propofol. This trial was conducted to evaluate the effect of propofol combined with remimazolam besylate on post-induction hypotension (PIH) in patients undergoing gynecological laparoscopic surgery. Methods All enrolled patients were randomly assigned to receive propofol (Group P), remimazolam besylate plus propofol (Group PR), or remimazolam besylate (Group R). Patients in group P received 2.0 mg/kg propofol, Sufentanil 0.4 μg/kg, and rocuronium bromide 0.8 mg/kg; Patients in group PR received remimazolam besylate 0.2 mg/kg, propofol 1.0 mg/kg, Sufentanil 0.4 μg/kg, and rocuronium bromide 0.8 mg/kg; Patients in group R received remimazolam besylate 0.4 mg/kg, Sufentanil 0.4 μg/kg, and rocuronium bromide 0.8 mg/kg; the anesthesia was maintained with propofol 4–10 mg/kg/h and remifentanil 0.1–0.3 μg/kg/min. The primary outcome was the incidence of hypotension after anesthesia induction. Hypotension was defined as a mean arterial pressure (MAP) reduced 30% or more from the baseline MAP value or MAP < 65 mmHg. Blood pressure was recorded five times during anesthesia. Time points T0, T1, T2, T3 and T4, were base line, before tracheal intubation, 1 min after tracheal intubation, 5 min after intubation, and immediately after surgical skin incision, respectively. The secondary outcomes were heart rate and bispectral index (BIS). Heart rate and BIS were measured from T0 to T4. Results One hundred sixty-nine patients were included in this study. A total of 30 patients in the three groups developed hypotension after anesthesia induction, among which the incidence of PIH induced in group P was 31.6% (18/57), the incidence of PIH induced in group PR was 14.3% (8/56), and the incidence of PIH induced group R 7.1% (4/56), and there was a statistical difference in the incidence of PIH between the three groups (χ2 = 12.24, p = 0.0022). The heart rates in group R (70.53 ± 13.36 bpm, 88.48 ± 13.53 bpm, and 72.68 ± 13.42 bpm) were significantly higher than that in group P (63.68 ± 10.76 bpm, 80.25 ± 12.50 bpm, and 66.35 ± 11.56 bpm) at T1, T2 and T4 (p < 0.05, respectively). The heart rate in group R (88.48 ± 13.53 bpm) was significantly higher than that in group PR (80.00 ± 13.42 bpm) at T2 (p < 0.05). There was no statistically significant difference between group PR and group P (p > 0.05). BIS was significantly higher in group R than that in group P and in group PR at T3 and T4 (p < 0.05, respectively). There was no statistically significant difference between group PR and group P (p > 0.05). Conclusions Both Propofol plus remimazolam besylate and remimazolam besylate alone can reduce PIH, but propofol plus remimazolam besylate smooths the heart rate after general anesthesia undergoing gynecological laparoscopic. Trial registration This trial was retrospectively registered at http://www.chictr.org.cn (06/06/2024, ChiCTR-2400085401).